(untitled) (Medical Forum Monthly, 2022)
Objective: To determine the frequency of complications of ileostomy in the management of ileal perforation secondary to typhoid fever in a tertiary setting. Study Design: Descriptive Study Place and Duration of Study: This study was conducted at the Department of Surgery, Bolan Medical College, Quetta from February 2020 to February 2021 for a period of one-year. Materials and Methods: Ninety patients with single or multiple ileal perforation due to typhoid fever confirmed by clinical features, laboratory tests and abdominal x-ray were included in this study. Patients were observed for complications of ileostomy like skin excoriation, stoma retraction, stenosis, prolapse, peristomal sepsis, parastomal hernia, necrosis and death for two months. Results: The average age of the patients was 40.30±10.14 years. Skin excoriation was the commonest complication that was observed in 18.9% cases followed by stoma retraction 10%, parastomal hernia 10%, stenosis 4.4%, prolapse 3.3%, peristomal sepsis 6.7% and necrosis 2.2%. Mortality was observed in 6.67% (6/90) due to stoma. Conclusion: In this study skin excoriation was the commonest complication. Early surgery and adequate resuscitation are the important factors for successful management of patients with ileal perforation. Primary closure of perforation is a preferred technique in clinically stable patients with a single perforation with minimal soiling of the abdominal cavity, to avoid complications related to stoma.